Systematic light-curve modelling of TDEs: statistical differences between the spectroscopic classes. Issue 4 (6th August 2022) - Nicholl, Matt; Lanning, Daniel; Ramsden, Paige; Mockler, Brenna; Lawrence, Andy; Short, Phil; Ridley, Evan J
ABSTRACT: With the sample of observed tidal disruption events (TDEs) now reaching several tens, distinct spectroscopic classes have emerged: TDEs with only hydrogen lines (TDE-H), only helium lines (TDE-He), or hydrogen in combination with He ii and often N iii /O iii (TDE-H + He). Here, we model the light curves of 32 optically bright TDEs using the Modular Open Source Fitter for Transients (mosfit ) to estimate physical and orbital properties, and look for statistical differences between the spectroscopic classes. For all types, we find a shallow distribution of star masses, compared to a typical initial mass function, in the range ∼0.1–1 M⊙, and no TDEs with very deep encounters. Our main result is that TDE-H events appear to come from less complete disruptions (and possibly lower SMBH masses) than TDE-H+He, with TDE-He events fully disrupted. We also find that TDE-H events have more extended photospheres, in agreement with recent literature, and argue that this could be a consequence of differences in the self-intersection radii of the debris streams. Finally, we identify an approximately linear correlation between black hole mass and radiative efficiency. We suggest that TDE-H may be powered by collision-induced outflows at relatively large radii, while TDE-H + He could result from prompt accretion discs, formed more efficiently in closer encounters around more massive SMBHs.